ACCOMMODATION VERSUS CONTROL SUGGESTED MODEL TO MACRO-ECONOMICS - Eltahir, Yassin (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2019)
The study raised the question of knowledge generation , in attempt to answer this question an economic model was introduced ,namely, aggregate demand and aggregate supply. The final target equations can be solved by general rule (deterministic) of solving quadratic equations. The study use analytical geometry and matrix algebra tools to solve the model beside testing their stability characteristics. If we reach unique value to the price equilibrium level then income equilibrium level the maximum potency of the economy can determined. Accordingly the rest of model values would be solved spontaneously. The essential derived result is the relationship between the dependent variable and independent variable can be redefined into accommodated and accommodator one. The long run growth rate of price and income which equal to the equilibrium combat with exogenous theory of growth which seeking stable and sustainable growth. Other results center around how to view the debate of diﬀerent economic schools from the shape of aggregate demand and aggregate supply, moreover the theoretical and practical test of model give great push to the suggested approach in answering the questions raised concerning the knowledge generation. If the model succeed in exceeding the theoretical and practical tests our understanding to the phenomena functioning will be broaden and enhanced, hence the model capability can be enlarged to interpret phenomena in fields other than economic, typically the suggested approach “ top to bottom” may contribute positively to the process of knowledge generation in addition to the modification of value system extraction. Finally the study suggested a protocol scenario in how to apply the derived model by introducing diﬀerent steps to the application.